ОСОБЕННОСТИ ГОСУДАРСТВЕННОГО РЕГУЛИРОВАНИЯ ИННОВАЦИОННОГО РАЗВИТИЯ ЭКОНОМИКИ: АНАЛИЗ МИРОВЫХ И ОТЕЧЕСТВЕННЫХ ПОДХОДОВ К ИСПОЛЬЗОВАНИЮ ЭКОНОМИЧЕСКИХ ИНСТРУМЕНТОВ В ИННОВАЦИОННОЙ ПОЛИТИКЕ (Journal of Economic Research & Business Administration, 2015)
The author in the article shines increase of a role of the state in the field of innovative activity, considers the mechanism of formation and realisation of a scientific and technical and innovative policy in the different countries of the world, offers world and domestic approaches to use of economic tools in the innovative policy.